Evaluation Of Some Medicinal Plants For Their Dandruff Control Properties - K. P. BALAKRISHNAN,; NITHYA NARAYANASWAMY,; SOOSAMMA MATHEWS,; KARUNA GURUNG, (International Journal of Pharma and Bio Sciences, 2011)
Dandruff caused by Malassezia spp is controlled by antifungal agents. In the present study four medicinal plants- Terminalia bellerica, Terminalia chebula, Emblica officinalis and Lantana camara- were selected to check their antifungal activity. Their efficacy was tested using different concentrations of extracts in various solvents. The antifungal activity of the plant extracts was determined by well diffusion method. Among the four plants screened, Terminalia bellerica and Terminalia chebula exhibited good antifungal action against the test organism. Emblica officinalis and Lantana camara did not show significant antidandruff activity. Aqueous and ethanolic extract of a combination of Terminalia bellerica with Lantana camara, and Terminalia chebula with Lantana camara were tested for their synergistic antidandruff activity. Results of the synergistic studies indicated that synergy exists between ethanolic extracts of Terminalia chebula and Lantana camara. From the study, it was found that Terminalia bellerica and Terminalia chebula act as the good sources of antidandruff agents.